Традиції бродячого ремесла на території України - Ольговський, С.Я. (Сіверщина в історії України, 2020)
У статті визначено рівень розвитку і роль ливарного ремесла на різних етапах розвитку суспільства. Виділено окремо діяльність бродячих ливарників і охарактеризовано чинники, що свідчать про їхню роботу. Традиция бродячого ремесла виникла разом
із появою металургії і металообробки та існувала протягом епох
енеоліта, бронзи і раннього залізного віку. The article defines the level of development and the role of foundry
craft at different stages of society development. Particular attention
was paid to successive divisions of labor, as a result of which narrow
specialists stood out - miners, metallurgists, foundry workers, among
which also narrower specialists stood out - gunsmiths, jewelers, etc. The
activities of vagrant craftsmen were singled out and evidence of their
work was characterized. Despite the regular process of the division of
labor among metallurgists, the casters, who led a mobile lifestyle, were
to some extent universal. The tradition of vagrant craft along with the
advent of metallurgy arose along with the advent of metallurgy and
metalworking and existed throughout the Neolithic, Bronze and Early
Iron Age eras. In a strange way, researchers never denied the work of
vagrant craftsmen in the Neolithic - Bronze Age, but they never raised
the issue of vagrant craftsmen in the early Iron Age. However, numerous
artifacts allowed to do this with sufficient categorization.
Convincing evidence of the work of vagrant craftsmen in the Bronze
Age was found in the burial of foundry workers, accompanied by craft
accessories, as well as foundry molds and semi-finished products in
settlements in the absence of stationary workshops. For the early Iron
Age, only one foundry burial can be named, but quite a lot of random
founding of foundry molds are known, and besides there is vivid evidence
of the foundry’s work in such seasonal festivities as the Yahorlytsky
settlement at the mouth of the Dnieper in the VI century BC and in
Kamenske settlement on the Dnieper in IV century BC. At the same
time, there are many stationary workshops in Scythia now nowadays
which allow talking about the developed foundry craft among the local
population as opposed to ancient craft in the Greek colonies of the
Northern Black Sea region.